Blue Economy Sebagai Strategi China Dalam Belt And Road Initiative Maritime - Firdausi, Farhan (Faculty of Social and Political Sciences - Universitas Wahid Hasyim, 2024)
Maritime strategy is not just a marine warfare strategy, but can be used as a commercialization effort of a country such as improving the economy. The Chinese government has a project to revive the Maritime Silk Road by connecting sea shipping lanes from coastal China to the rest of the world covering the continents of Asia, Europe, Africa and America which aims to facilitate China's International Trade access to the Global Market. In an effort to revive the Maritime Silk Road, the Chinese Government uses the Maritime Belt and Road Initiative as their effort to revive and expand the route. The Belt and Road Initiative Maritime uses the concept of Blue Economy as the Chinese Government's strategy in cooperating with partner countries in the success of the Belt and Road Initiative Maritime. The Blue Economy concept is used by the Chinese Government in the Belt and Road Initiative Maritime because it utilizes the sea in their International Trade. Blue Economy is a concept in maritime that utilizes the sea as a means of improving a country's economy. In addition, the Chinese Government uses the Blue Economy to preserve the oceans to utilize the potential of the sea so that it can be used sustainably. In this research, the author will explain how China uses Blue Economy in the Belt and Road Initiative Maritime project. Keywords: Belt and Road Initiative Maritime, Blue Economy, International Trade.